2004
DOI: 10.1385/mo:21:1:09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mesna on the Pharmacokinetics of Cisplatin and Carboplatin in Pediatric Cancer Patients

Abstract: Mesna, a reactive thiol, often encounters cisplatin and carboplatin in combination protocols involving oxazaphosphorines and platinum drugs. This co-administration might be unfavorable based on the inactivation of platinum drugs by thiol groups in vitro. We investigated whether mesna influences the pharmacokinetics of platinum drugs when co-administered with cisplatin or carboplatin. The pharmacokinetics of platinum drugs were investigated in 18 pediatric patients receiving either cisplatin or carboplatin in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Though the protection of mesna was achieved without attenuating the efficacy of co-administered anti-cancer agents such as ifosfamide and cyclophosphamide [20], there was inconsistence in the effect on platinum chemotherapeutic agents. It was reported that the active thiol monomer of mesna could bind to platinum drugs and reduce their efficacy by a direct reaction with platinum molecule [37,38] while Kangarloo et al [39] ruled out the influence of mesna on the pharmacokinetics of cisplatin and carboplatin. In the present study, we measured the influence of cisplatin and mesna on the cisplatin sensitive HepG2 cell line either with single administration or co-administration.…”
Section: Discussionmentioning
confidence: 99%
“…Though the protection of mesna was achieved without attenuating the efficacy of co-administered anti-cancer agents such as ifosfamide and cyclophosphamide [20], there was inconsistence in the effect on platinum chemotherapeutic agents. It was reported that the active thiol monomer of mesna could bind to platinum drugs and reduce their efficacy by a direct reaction with platinum molecule [37,38] while Kangarloo et al [39] ruled out the influence of mesna on the pharmacokinetics of cisplatin and carboplatin. In the present study, we measured the influence of cisplatin and mesna on the cisplatin sensitive HepG2 cell line either with single administration or co-administration.…”
Section: Discussionmentioning
confidence: 99%
“…The cycle was placed at the end of the radiation treatment because it was expected to cause bone marrow suppression; this would have cause a risk for interruption of radiation if the cycle was given earlier 22. The infusion times of ifosfamide and cisplatin were separated by positioning the etoposide infusion in between, so that mesna was not infused during cisplatin infusion or at times of peak plasma levels 26, 27. After radiation therapy, the chemotherapy continued with further cycles of PEI in Weeks 10, 14, 18, 22, 26, and 30, as well as vincristine in Weeks 13, 17, 21, 25, and 29.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, mesna does not interfere with the pharmacokinetics of cisplatin. 19,24,25 We sought to address the effects of multiple exposures to cisplatin on the future reproductive capabilities by studying adverse effects of prior injections of cisplatin on the reproductive function of female rats. In addition, we sought to determine the degree of protection against the adverse reproductive effects of cisplatin by using mesna.…”
Section: -23mentioning
confidence: 99%